SPATIAL TRANSFORMATION OF THE CATUSPATHA AREA AS THE CITY CENTER OF TABANAN - Putu Prilia Widariyathi; Ardhya Nareswari (Jurnal Planologi, 2026)
Urban centers in Bali, such as Tabanan, are closely associated with Catuspatha, which represents the identity of traditional Balinese spatial planning. However, historical, political, social, and modernization processes have driven complex spatial transformations. This study offers novelty by comprehensively examining the relationship between land use, road networks, and open space transformations about the meaning, function, and elements of Catuspatha, framed within central place theory. The objective is to analyze spatial dynamics from the kingdom era (1493–1906), colonial period (1906–1929), to the modern era (2002–2025), along with the non-physical factors influencing these changes. A qualitative-descriptive method was employed through synchronic and diachronic analysis, supported by field observation, archival research, mapping, and in-depth interviews with local figures. The results reveal that land use shifted from a concentric model centered on the puri to a colonial sectoral pattern, and later to a multifunctional polycentric structure. The road network evolved from the traditional Catuspatha into a modern grid, while open space experienced significant fluctuations—expansive in the royal era, reduced by 45% in 2002, and revitalized through the construction of Bung Karno City Park in 2025. In conclusion, although the functions and settings of Catuspatha have shifted toward trade, services, and mobility, its cosmological meaning endures, consistent with central place theory that emphasizes dynamic and multifunctional urban centers.Keywords: Spatial Transformation, City Center, Catuspatha Concept, Tabanan  Pusat-pusat kota di Bali, salah satunya di Tabanan identic dengan keberadaan Catuspatha yang merepresentasikan identitas tata ruang tradisonal Bali, namun perkembangan sejarah, politik, sosial, dan modernisasi telah mendorong transformasi spasial yang kompleks. Penelitian ini memiliki kebaruan karena mengkaji keterkaitan transformasi guna lahan, jaringan jalan, dan ruang terbuka terhadap makna, fungsi, dan elemen Catuspatha secara komprehensif dengan pendekatan teori pusat kota. Tujuan penelitian adalah menganalisis dinamika perubahan spasial dari masa kerajaan (1493–1906), kolonial (1906–1929), hingga era modern (2002–2025), serta faktor non-fisik yang memengaruhinya. Metode yang digunakan adalah kualitatif-deskriptif melalui analisis sinkronik dan diakronik, dilengkapi observasi lapangan, studi arsip, pemetaan, dan wawancara mendalam dengan tokoh lokal. Hasil penelitian menunjukkan transformasi guna lahan bergeser dari pola kosentris berbasis puri, ke model sektoral kolonial, hingga inti ganda multifungsi modern. Jaringan jalan berubah dari pola tradisional Catuspatha ke grid modern, sementara perubahan ruang terbuka menunjukkan dinamika yang cukup signifikan, bermula dari keberadaan ruang terbuka yang luas, kemudian mengalami penyusutan sebesar 45% pada tahun 2002, hingga akhirnya dipulihkan kembali melalui pembangunan Taman Kota Bung Karno pada tahun 2025. Kesimpulan utama menegaskan bahwa meski fungsi dan setting Catuspatha bergeser menuju pusat perdagangan, jasa, dan mobilitas, makna filosofisnya sebagai simbol kosmologis tetap bertahan, sekaligus konsisten dengan teori pusat kota yang menekankan sifat dinamis dan multifungsi.Kata kunci: Transformasi Spasial, Pusat Kota, Konsep Catuspatha, Tabanan